Avaliação da medida da hipotenusa da escavação vertical do nervo óptico utilizando o modo de imagem profunda realçada da tomografia de coerência óptica de domínio espectral: um potencial novo parâmetro estrutural na propedêutica do glaucoma - Lavinsky, Fabio [UNIFESP] (2016)
Purpose: To evaluate the measurement of the hypotenuse of the vertical optic nerve head cupping (HVOC) with the enhanced depth imaging (EDI) mode of the spectral domain optic coherence tomography (SD-OCT) as a novel structural parameter for glaucoma evaluation. Methods: We conducted a prospective, cross-sectional study with patients diagnosed with glaucoma and controls. Patients underwent SD-OCT evaluating the mean thickness of the retinal nerve fiber layer (RNFL) and the HVOC. One leg of the triangle represented the depth and the other leg represented the length of the cupping. These legs were manually measured. Patients also underwent color pictures and standard automated perimetry (SAP). The evaluation was performed in 85 patients (156 eyes). Patients were divided into three groups: 1) MD < -7 dB, 2) MD > -7 dB, and 3) patients without glaucoma. The structure-function evaluation and the evaluation with the receiving operating curve (ROC) excluded eyes with the vertical diameter of the optic nerve > 2.0 and < 1.5. Results: The mean and median SD-OCT RNFL values were: group 1) 62.0±3.3 ?m, 54.0 (49.0; 75.8); group 2) 84.4±1.8 ?m, 85.0 (74.0; 94.0), and group 3) 96.6±2.3 ?m, 97.0 (90.5; 102.0) (p<0.001). The mean of the MD were: group 1) -16.7 dB, group 2) -2.5 dB, and group 3) -1.7 dB (p<0.001). The correlation of the SD-OCT RNFL and the SAP was statistically significant (p<0.0001 and r=0.681). The means of the HVOC were divided in three different vertical optic nerve diameter (VD) ranges (<1.5 mm, 1.51-2.00 mm, and >2.00 mm). Within each nerve diameter range the difference of the HVOC from the different groups was statistically significant. For the structural-functional correlation and for the evaluation of the ROC curves only nerves with a VD of 1.51-2.00 mm were evaluated (120 eyes). The HVOCs were divided into four percentile groups with the following medians in ?m: 925 (298-1,079); 1,162 (1,085-1,271); 1,415 (1,273-1,522); and 1,624 (1,527-1,993). There was a statistically significant difference of the values of the MD in each percentile group between group 1 and 3 (p<0.03), group 1 and 4 (p<0.001), group 2 and 3 (p<0.02), and between group 2 and 4 (p<0.001). In those eyes, the correlation between the HVOC and the SD-OCT RNFL was r =-.64 (p<0.001). The areas under the curve (AUC) of the ROC curve and the 95%CI evaluating the HVOC were: for positive cases with MD < -3 dB = 0.76 (0.64-0.85), MD < -6 dB = 0.77 (0.68-0.87), and MD < -12 dB= 0.79 (0.70-0.89). The ROC curves of the SD-OCT RNFL were compared with the HVOC using the DeLong test. There was no statistically significant difference, for positive cases determined as MD < -12 dB, there was a borderline difference (p=0.06). Conclusions: The HVOC provides a simple numeric parameter obtained from two important hallmarks of the glaucomatous nerve: the vertical length of the cupping and the depth of the cupping. In our study, we found a structural-functional correlation of the HVOC with the MD of the SAP, as well as with the RNFL. The AUCs of the HVOC were comparable with those of the RNFL. The HVOC has a potential to be used as an additional topographic parameter of the structural evaluation of glaucoma.